Effect of a novel nonviral gene delivery of BMP-2 on bone healing - Schwabe, Philipp; Schmidmaier, Gerhard (The ScientificWorld journal, 2012)
Background. Gene therapeutic drug delivery approaches have been introduced to improve the efficiency of growth factors at the site of interest. This study investigated the efficacy and safety of a new nonviral copolymer-protected gene vector (COPROG) for the stimulation of bone healing. Methods. In vitro, rat osteoblasts were transfected with COPROG